Sanitary quality of Brachiaria brizantha cv. Marandu and Xaraés seeds harvested in different states in Brazil (Bioscience Journal, 2017)
The incidence of fungi in seeds depends on the sanitary and climatic conditions in which the seeds were produced. So, the objective of this study was to identify the fungi present in commercial lots of Brachiaria brizantha cv. 'Marandu' and'Xaraés' seeds harvested in different areas in Brazil. Seeds from ten lots of each cultivar, produced in the Brazilian states of Mato Grosso do Sul, Mato Grosso, Goiás, Minas Gerais, São Paulo, and Bahia were evaluated as to moisture content, germination and sanity. The experiment was conducted according to a completely random design with eight replications of 50 seeds for each lot. In both cultivars, the seeds were found to be infected with Aspergillus sp., Chaetomium sp., Curvularia sp., Fusarium sp., and Helminthosporium sp; the highest incidences were those of Chaetomium Â sp. and Fusarium sp. Seeds of the 'Marandu' cultivar were the only ones showing the presence of Phoma sp. and Pyricularia grisea and those of the 'Xaraés' cultivar with Colletotrichum sp. and Nigrospora sp. The incidence of Fusarium sp., Aspergillus and Nigrospora sp. reduces 'Xaraés' seeds germination whereas it does not interfere in the 'Marandu' seeds germination.Â  The presence of the fungus Pyricularia grisea is for the first time reported in tropical forage grass seeds produced in the Southeast and Northeast regions of Brazil.